The determinants of corporate cash holdings: An empirical investigation of the industry effect of UK publicly held firms (1998-2013) - WANG, ZIWEN (2015)
Abstract This paper investigates the determinants of cash holdings by publicly traded firms over the period 1998-2013. The results suggest that cash holdings are positively affected by investment opportunity set, capital expenditure and profitability and negatively affected by the real firm size, liquid assets substitutes, leverage level, cash flow and dividend payments, which are generally in line with previous studies. In addition, we observed the change of corporate cash holdings during the global financial crisis period. Moreover, cash holdings tend to vary across industries.